2019
DOI: 10.1002/adfm.201906148
|View full text |Cite
|
Sign up to set email alerts
|

Excited State Dynamics of a Self‐Doped Conjugated Polyelectrolyte

Abstract: The growing number of applications of doped organic semiconductors drives the development of highly conductive and stable materials. Lack of understanding about the formation and properties of mobile charges limits the ability to improve material design. Thus the largely unexplored photophysics of doped systems are addressed here to gain insights about the characteristics of doping‐induced polarons and their interactions with their surroundings. The study of the ultrafast optical processes in a self‐doped conj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 57 publications
(93 reference statements)
3
40
2
Order By: Relevance
“…In contrast to the findings of Tsokkou et al, who evaluated acid doping of the donor-acceptor system PCPDTBT, 38 we do not observe a broad bleaching feature corresponding to the energy of the polaron (SI Figure S18). In fact, for ProDOT(OE3)-DMP, we see no evidence for a shared ground state between the exciton and polaron.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast to the findings of Tsokkou et al, who evaluated acid doping of the donor-acceptor system PCPDTBT, 38 we do not observe a broad bleaching feature corresponding to the energy of the polaron (SI Figure S18). In fact, for ProDOT(OE3)-DMP, we see no evidence for a shared ground state between the exciton and polaron.…”
Section: Discussioncontrasting
confidence: 99%
“…What seems to be common to both the acid-doped PCPDTBT 38 and our analysis of electrochemically doped ProDOT(OE3)-DMP is the effect of charge concentration on the dynamics of the PB. In both cases, doping is associated with a quenching of the PB, which is to be expected given the general phenomenon of exciton-charge annihilation.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…At present, it is not clear why the formation of bipolarons with B(C 6 F 5 ) 3 as dopant (or other molecular dopants, as discussed in the Introduction) does not happen. We speculate that this could be attributed i) to a higher effective oxidation strength of Mes 2 B + [B(C 6 F 5 ) 4 ] − compared to other dopants (facilitating the creation of further holes in the already highly doped P3HT), ii) to the bulkiness of the [B(C 6 F 5 ) 4 ] − anion and thus a different electrostatic potential landscape on the molecular length scale in films, [76] and iii) to dopant-induced changes in morphology that render bipolaron formation more favorable. We recall at this point our observations in absorption spectra, which indicated that beyond ≈5% dopant concentration aggregation of P3HT was effectively suppressed.…”
Section: Doping Mechanismmentioning
confidence: 99%